Simulation of Katabatic Winds at Mizuho Station, Antarctica - Yimin, Ma (Polar Research Institute of China - PRIC, 1992)
A new simulation method for solving dynamic equations for stationary katabatic wind is suggested by the assumption that the turbulent exchange coefficient is a function of height and the effect of the cold sloping surface is a multinormal function of height. Calculated wind profiles agree with observational data at Mizuho Station, Antarctica.